Toxicity of Selected Insecticides against Cotton Thrips (Thrips tabaci Lindeman) in Laboratory Bioassays - Chauhan, S. N.; Bhanderi, G. R.; Patel, R. D.; Desai, H. R. (International Journal of Economic Plants, 2022)
Investigations on toxicity of insecticides against cotton thrips (Thrips tabaci Lindeman) was carried out at laboratory of Main Cotton Research Station, Navsari Agricultural University, Surat during August to October 2020 through the IRAC leaf dip bio-assay technique. Thrips population from the farmer’s field of Bharuch district were collected and reared at Main Cotton Research Station, NAU, Surat under field cage cover. Leaf dip bio-assays were carried out for the five insecticides viz., fipronil 5 SC, buprofezin 25 SC, diafenthiuron 50 WP, profenophos 50 EC and imidacloprid 17.8 SL with eight concentrations. At recommended rate, diafenthiuron 50 WP at 0.06% and profenophos 50 EC at 0.1% recorded 90.36 and 83.29% mortality of thrips at 72 hours after exposure. Buprofezin 25 SC at 0.05%, imidacloprid 17.8 SL at 0.00445% and imidacloprid 17.8 SL at 0.00445% recorded 79.81, 63.54 and 57.06% mortality of thrips under laboratory bioassay at 72 hours after exposure. The recommended rate of the test insecticides except fipronil 5 SC and imidacloprid 17.8 SL did not show much variation in susceptibility at 72 hours after exposure.